Evaluation of angiogenesis in cervical cancer using CD34 as a biomarker and its correlation with pathoanatomical features - Mohsin Aijaz; Kiran Alam; Veena Maheshwari (Annals of Cytology and Pathology - Peertechz Publications, 2021)
Aim: CD34 is an antigen found in hematopoietic progenitor cells and endothelial cells. Anti-CD34 antibody is a highly sensitive marker for neovascularisation and has also been studied as a marker for vascular tumours. However, there are few studies relating it to cervical carcinoma. The aim of our study is to evaluate the CD34 expression as a marker of angiogenesis in cervical cancer and to correlate the microvessel count and Microvessel Density (MVD) with histopathological type and grade of tumour and lymph node metastasis.  Method: Total 75 malignant cases (65 cases of squamous cell carcinoma and 10 cases of adenocarcinoma) were stained with anti CD34 antibody to highlight the blood vessels. In each case, areas of highest neo-vascularization were identified using scanner lens. Blood vessels were counted in 10 microscopic fields at 400X magnification. Average number of non-canalized micro-vessels count per field was calculated (MVD). Result: The total number of microvessels stained per case ranged from 54 to 216. No statistically significant differences were observed for MVD with respect to the age of patient and histological type of carcinoma (p > 0.05). The mean vascular density in differentiated carcinoma and undifferentiated carcinoma, was 10.56 and 14.14 respectively. This clearly shows that the distribution of microvessels was higher among undifferentiated carcinomas, as compared to differentiated carcinoma (p < 0.05). Furthermore, the MVD in lymph node positive cases was 12.84, slightly higher as compared to lymph node negative cases where it was 11.34. However, the relationship was statistically nonsignificant (p > 0.05). Conclusion: CD 34 can be used as a novel marker for estimation of MVD in cervical cancer, however further studies are required on large group of patients to establish its role as a therapeutic target against angiogenesis.